Axonal conduction in multiple sclerosis: A combined magnetic resonance imaging and electrophysiological study of the medial longitudinal fasciculus. (June 2015) - Wang, Chenyu; Paling, David; Chen, Luke; Hatton, Sean N; Lagopoulos, Jim; Aw, Swee T; Kiernan, Matthew C; Barnett, Michael H
Objective: The objective of this paper is to inform the pathophysiology of medial longitudinal fasciculus (MLF) axonal dysfunction in patients with internuclear ophthalmoplegia (INO) due to multiple sclerosis (MS), and develop a composite structural-functional biomarker of axonal and myelin integrity in this tract. Methods: Eighteen patients with definite MS and clinically suspected INO underwent electrical vestibular stimulation and search-coil eye movement recording. Components of the electrically evoked vestibulo-ocular reflex (eVOR) were analyzed to probe the latency and fidelity of MLF axonal conduction. The MLF and T2 -visible brainstem lesions were defined by high-resolution MRI. White matter integrity was determined by diffusion-weighted imaging metrics. Results: eVOR onset latency was positively correlated with MLF lesion length (left: r = 0.66, p = 0.004; right: r = 0.75, p = 0.001). The mean conduction velocity (±SD) within MLF lesions was estimated at 2.72 (±0.87) m/s. eVOR onset latency correlated with normalized axial diffusivity ( r = 0.66, p < 0.001) and fractional anisotropy ( r = 0.44, p = 0.02) after exclusion of cases with ipsilateral vestibular root entry zone lesions. Conclusions: Axonal conduction velocity through lesions involving the MLF was reduced below levels predicted for natively myelinated and remyelinated axons. Composite in vivo biomarkers enable delineation of axonal from myelin processes and may provide a crucial role in assessing efficacy of novel reparative therapies in MS.